A Co-Requisite Model for Developmental Mathematics: Innovative Pathway Leads to Positive Outcomes for Education Majors - Atkins, Charlene; McCoy, Ann (Educational (Re)naissance, 2017)
The traditional mathematics pre-requisite model creates obstacles for pre-service educators by increasing the number of semesters to graduation. Extended time results in additional financial burdens for students in developmental courses along with increased risk of student drop out. Education majors, with little or no room for electives in their programs of study, have been particularly impacted. The pilot of a co-requisite model, involving the collaboration of two academic departments, has proven successful in enhancing students’ academic achievement while addressing social and emotional needs of students.